2008
DOI: 10.1093/pcp/pcm162
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and Cell-Specific Localization of Rice Aquaporins and Their Water Transport Activities

Abstract: Water transport in plants is greatly dependent on the expression and activity of water transport channels, called aquaporins. Here, we have clarified the tissue- and cell-specific localization of aquaporins in rice plants by immunoblotting and immunocytochemistry using seven isoform-specific aquaporin antibodies. We also examined water transport activities of typical aquaporin family members using a yeast expression system in combination with a stopped-flow spectrophotometry assay. OsPIP1 members, OsPIP2;1, Os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 47 publications
(62 reference statements)
5
108
0
1
Order By: Relevance
“…4, E-G). In agreement with the previous report, OsPIP1;2 was found to be expressed and trafficked to the yeast membrane with similar efficiency as OsPIP2s, but the water transport activity of OsPIP1;2 was smaller than OsPIP2s (9). Our data further affirmed that OsPIP1s are less permeable to water than OsPIP2s partly due to the Ala/ Ile(Val) difference.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…4, E-G). In agreement with the previous report, OsPIP1;2 was found to be expressed and trafficked to the yeast membrane with similar efficiency as OsPIP2s, but the water transport activity of OsPIP1;2 was smaller than OsPIP2s (9). Our data further affirmed that OsPIP1s are less permeable to water than OsPIP2s partly due to the Ala/ Ile(Val) difference.…”
Section: Discussionsupporting
confidence: 92%
“…Size exclusion at the two main constrictions is one of the mechanisms for water transport and substrate selectivity by AQPs (3,4). Extensive investigation of the plant PIPs revealed that PIP2 paralogues induced water permeation when expressing on Xenopus oocyte or yeast membranes, whereas PIP1 paralogues were almost inactive (5)(6)(7)(8)(9)(10). The sequence difference between the two subgroups, however, is quite subtle, as they share the same residues in main pore constrictions and almost the same hydrophobic residues around the aqueous pathway (6,11).…”
mentioning
confidence: 99%
“…Previous studies (Sakurai et al, 2005(Sakurai et al, , 2008Guo et al, 2006;Sakurai-Ishikawa et al, 2011) and our own preliminary experiments (not shown) on the Bala rice cultivar analysed showed that all three PIP1 genes and all PIP2 genes except OsPIP2;7 and OsPIP2;8 are expressed in roots at significant, or at least reproducibly detectable levels. Therefore, the latter two rice PIP genes were not included in the present analyses.…”
Section: Introductionmentioning
confidence: 53%
“…In rice, OsPIP1;3 and OsPIP2;4 are the two PIP genes, besides OsPIP2;5, which show the largest, and significant decrease in expression in response to treatments which reduce shoot transpirational water loss. Similarly to OsPIP2;5, OsPIP1s (including OsPIP1;3) and GmPIP1;6 are localized in most root tissues and in particular in the endodermis; GmPIP1;6 is also localized in stelar tissue (Sakurai et al, 2008;Vandeleur et al, 2014). Together these data point to PIP AQPs, which are localized in the endodermis or stele, as the prime facilitators for mediating the decrease in root Lp in response to shoot removal and changes in shoot transpirational demand.…”
Section: Rice Root Pip Aqp Expression In Response To Shoot Removalmentioning
confidence: 79%
See 1 more Smart Citation